Implementasi Wathaniyah dalam Mewujudkan Kemandirian Pesantren: Studi di Pesantren Riyadlul Jannah Mojokerto - Budiyono Santoso (Peradaban Journal of Religion and Society, 2026)
This study aims to analyze the implementation of wathaniyah (religious-based nationalism) in fostering institutional independence at Pesantren Riyadlul Jannah. Departing from the understanding that pesantren serve not only as religious educational institutions but also as socio-national actors, wathaniyah is positioned as a religious value with social and institutional implications. The research employs a qualitative phenomenological approach through in-depth interviews, observation, and documentation, and the data were analyzed using thematic-phenomenological techniques. The findings reveal that wathaniyah functions as both a normative and ideological foundation for pesantren independence. Love of the homeland is understood as part of faith and religious responsibility, manifested in economic autonomy, social welfare commitments, and active contributions to national development. Such independence is not perceived as a purely pragmatic objective but as a means to safeguard the pesantren’s ethical autonomy and freedom of service to society and the state. This study demonstrates that wathaniyah operates as a religious ethic that drives pesantren empowerment. The findings contribute to the fields of religious and social studies by showing how contextualized religious values can serve as normative foundations for strengthening pesantren roles within Indonesian civic life. Penelitian ini bertujuan menganalisis implementasi wathaniyah dalam mewujudkan kemandirian kelembagaan di Pesantren Riyadlul Jannah. Berangkat dari asumsi bahwa pesantren merupakan aktor keagamaan sekaligus kebangsaan, penelitian ini memposisikan wathaniyah sebagai nilai keagamaan yang memiliki implikasi sosial dan kelembagaan. Penelitian menggunakan pendekatan kualitatif fenomenologis melalui wawancara mendalam, observasi, dan studi dokumentasi, kemudian dianalisis secara tematik-fenomenologis. Hasil penelitian menunjukkan bahwa wathaniyah berfungsi sebagai landasan normatif dan ideologis bagi pembangunan kemandirian pesantren. Nilai cinta tanah air dipahami sebagai bagian dari iman dan tanggung jawab keagamaan, dan diwujudkan dalam kemandirian ekonomi, komitmen terhadap kesejahteraan sosial, serta kontribusi terhadap pembangunan nasional. Kemandirian dimaknai bukan sekadar tujuan pragmatis, tetapi sebagai cara menjaga otonomi nilai dan kebebasan pengabdian pesantren kepada umat dan bangsa. Studi ini menegaskan bahwa wathaniyah dapat berperan sebagai etika keagamaan yang mendorong kemandirian pesantren. Temuan ini memperkaya kajian agama dan sosial dengan menunjukkan bahwa nilai keagamaan mampu menjadi basis normatif bagi penguatan peran pesantren dalam kehidupan kebangsaan di Indonesia.